The Effect of the Combination of Two Postbiotics on Anxiety-like Behavior in Animal Models - Vanesa Robles; Ferran Balaguer; Miren Maicas; Juan Manuel Martínez-Vázquez; Patricia Martorell; Marta Tortajada; Daniel Ramón; David G. Valcarce (Cells)
With increasing evidence showing the connections between the microbiome, neurophysiology, and behavior, our research endeavors to investigate whether the consumption of a combination of two postbiotics with antioxidant effects can affect behavior regulation in model species. Here, we worked with a combination (1:1 ratio) of heat-treated Bifidobacterium longum subsp. longum ES1 (CECT7347) and Lacticaseibacillus rhamnosus BPL15 (CECT8361) as a dietary supplement. To examine the potential benefit of using this formulation to alleviate anxiety-like behavior, we employed two model species, Caenorhabditis elegans and adult Danio rerio. In C. elegans, the postbiotic supplementation reduced the anxiety-related behavior analyzed by means of the octanol avoidance test. In zebrafish, the novel tank test indicated a different swimming pattern 2 and 4 months after the animals were fed with the postbiotic combination. While fish did not exhibit any variance in their locomotion parameters such as pace and speed, they showed a statistically significant preference to spend more time in the upper zone of the water tank, a behavior that is correlated with a lower anxiety-like behavior in these species. Our aim with this study is to present evidence that can be used to develop whole-cell postbiotic-based novel and innovative dietary supplements for anxiety-related conditions.